Study on Metabolic Trajectory of Liver Aging and the Effect of Fufang Zhenzhu Tiaozhi on Aging Mice - Luo, Duosheng; Li, Jingbiao; Chen, Kechun; Yin, Yifan; Fang, Zhaoyan; Pang, Huiting; Rong, Xianglu; Guo, Jiao (Frontiers in Pharmacology, 2019)
The aim of this study was to investigate the metabolic trajectory of liver aging, the anti-liver aging effect of FTZ in aging mice and its mechanism using UPLC-TOF/MS. Methods: A total of 80 C57BL/6J Narl mice were randomly divided into 5 groups: 3 months old group, 9 month old group, 14 month old group, 20 month old group and FTZ treatment group (20 month old). The mice in the treatment group received a therapeutic dose of oral FTZ extract (1.0 g/kg, on raw material weight basis) once daily during the experiment. The other groups received the corresponding volume of oral normal saline solution. Liver samples of all five groups were collected after 12 weeks, and ultra-performance liquid chromatography-tandem mass spectrometry (UPLC–MS/MS) was used to analyze metabolic changes. Orthogonal partial least squares discriminant analysis (OPLS-DA) was used to analyze the resulting data. Additionally, cholesterol triglyceride, aspartate aminotransferase(AST), alanine aminotransferase(ALT),secretion levels of TNF-α,IL-6, 5-LOX, COX-2 and relative mRNA expression in liver were detected. Results: The levels of TC, TG, AST, ALT were increased, and liver tissue structure was damaged, secretion levels of TNF-α, IL-6, 5-LOX, COX-2 and relative mRNA expression in liver also increased with aging. FTZ administration reduced the risk of liver-aging. The OPLS-DA score plot indicated the anti-liver aging effect of FTZ with N-acetyl-leukotriene E4, 20-hydroxy-leukotriene E4, leukotriene E4, and arachidonic acid among the key biomarkers. The pivotal pathways revealed by pathway analysis included arachidonic acid metabolism and biosynthesis of unsaturated fatty acids. The mechanism by which FTZ reduces the risk of liver aging in mice might be related to disorders of the above-mentioned pathways. Conclusion: A metabolomic approach based on UPLC-QTOF/MS and multivariate statistical analysis was successfully applied to investigate metabolic trajectory of liver aging. FTZ has a protective effect against liver aging, which may be mediated via interference with the metabolism of arachidonic acid, biosynthesis of unsaturated fatty acids and downregulation of pro-inflammatory factors in the liver in mice in vivo.